Effect of changing reference growth charts on the prevalence of short stature - Pilar Aizpurua Galdeano; Maider Mateo Abad; Ángeles Alonso Alonso; Saioa Juaristi Irureta; Begoña Carvajal Goikoetxea; Sara García Ruiz; Sorkunde Jaca Miranda (Elsevier, 2020)
Introduction: Short stature is a family concern, and is a common reason for consultations in paediatrics. Growth charts are an essential diagnostic tool. The objective of this study is to evaluate the impact of changing reference charts in the diagnosis of short stature in a health area. Subjects and methods: A population-based-cross-sectional-descriptive-study was performed in which the height of children of 4, 6, 10 and 13 years-old were compared with the growth charts of the Fundación Orbegozo 2004 Longitudinal and 2011. The prevalence of short stature and the 3rd percentile of the study sample were calculated. Results: There were 12,256 valid records (89% of the population). The prevalence of short stature increased at all ages with the change in the growth charts, with differences of prevalence of 3.6% (95% CI: 2.8-4.5) at 4 years; 1.8% (95% CI: 1.3-2.3) at 6 years; 2.8% (95% CI: 2.2-3.4) at 10 years, and 1.4% (95% CI: 0.8-1.9) at 13 years. In absolute numbers, it went from 58 diagnoses of short stature with the 2004 Longitudinal charts (34 boys and 24 girls) to 352 with the 2011 (155 boys and 197 girls). Conclusions: The change in reference growth charts has increased by 6-fold the number of diagnoses of short stature. The pathological condition found in the cases diagnosed with the 2011 growth charts that had not been diagnosed with the previous charts will allow us to evaluate the suitability of the change. Resumen: Introducción: La talla baja es motivo de preocupación familiar y constituye una consulta frecuente en pediatría. Para su diagnóstico las gráficas de crecimiento son una herramienta imprescindible. El objetivo de este estudio es evaluar el impacto del cambio de gráficas de referencia en el diagnóstico de talla baja en nuestra área de salud. Sujetos y métodos: Estudio descriptivo transversal de base poblacional. Los valores de la talla de los niños y niñas de 4, 6, 10 y 13 años se compararon con las tablas de la Fundación Orbegozo 2004 Longitudinal y 2011. Se calcularon las prevalencias de talla baja y el percentil 3 de la muestra del estudio para realizar las comparaciones. Resultados: Se obtuvieron 12.256 registros válidos (89% de la población). La prevalencia de talla baja aumentó en todas las edades con el cambio de las gráficas: diferencia de prevalencias del 3,6% (IC95%: 2,8 a 4,5) a los 4 años; 1,8% (IC95%: 1,3 a 2,3) a los 6 años; 2,8% (IC95%: 2,2 a 3,4) a los 10 años y 1,4% (IC95%: 0,8 a 1,9) a los 13 años. En números absolutos, se pasó de 58 diagnósticos de talla baja con las gráficas 2004 (34 niños y 24 niñas) a 352 con las 2011 (155 niños y 197 niñas). Conclusiones: El cambio de referencia ha multiplicado por 6 el número de diagnósticos de talla baja. La patología hallada en los casos diagnosticados con las gráficas 2011 que no se hubieran diagnosticado con las gráficas anteriores nos permitirá evaluar la idoneidad del cambio realizado.